Mind the gap: State of the art on decision-making related to post-disaster housing assistance. (1st February 2021) - Pezzica, Camilla; Cutini, Valerio; Bleil de Souza, Clarice
Abstract: A growing awareness of the long-term impact of emergency management plans is shifting the focus of post-disaster housing studies towards integrated recovery and development. These would benefit from knowledge about decision-making challenges and dichotomies which determine the success or failure of housing assistance programs, and of methods and tools that can support their holistic resolution. To establish common grounds in this area, this paper systematically reviewed the literature on temporary housing built after sudden natural hazards, from a decision-making perspective, using reflexive thematic analysis methods. This enabled the identification of critical decision-making components (i.e. open challenges, trade-offs, dilemmas and contradictions) and necessary synergies at three levels: the operational, the managerial and the strategic. Results highlight the value of a structured review of the literature to identify decision-making gaps and opportunities for knowledge integration across domains, besides the need of a constructive decision-making alignment at all decision-making levels to enable holistic recovery planning. Additionally, they show the importance of an in-depth examination of decision-making dichotomies for developing novel methods and tools, which respond to contextual needs and local dynamics. Being one of a few studies in a rather underexplored area of research, the primary aim of this review is to offer a broad and structured overview of decision-making issues documented in the literature to date, which connects both theory and practice. The results could be operationalised in future research aimed at supporting Build Back Better efforts towards a truly human-centred housing assistance culture, by investigating the connected decision-making dynamics in specific contexts. Highlights: Aligning strategic, managerial and operational decision-making is key to enable BBB. Interdisciplinary and transdisciplinary decision-making is essential to close gaps. Knowledge of decision-making dichotomies helps to develop novel methods and tools. Decision support tools should be responsive to contextual needs and local dynamics.